2018
DOI: 10.1016/j.fertnstert.2018.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst freeze-all strategy versus fresh transfer in anonymous oocyte donation cycles

Abstract: ploidy). Reports indicated the % of fragmented sperm DNA (DFI). Patients were divided into 2 groups: (<15% and >15%) and incidence of segmental aneuploidy was compared between the groups in 2 ways: 1) any segmental aneuploidy (among all embryos, including those with an additional whole chromosome aneuploidy) and 2) segmental aneuploidy only (no other whole chromosome aneuploidy).RESULTS: A total of 169 cases were included in the analysis. DFI <15% was found in 123 specimens, while DFI >15% was found in 45 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In the present study, when we analyzed the efficiency of oocyte cryopreservation in women at different age groups, we found that live birth rates can reach to 51.1, 46.7 and 28.6% in women <35, 35-37, and > 37 years old, respectively, with their first embryo transfer (fresh), which is comparable to live birth rates with embryo transfer from fresh oocytes in our clinic or other published data [2,3,9,23,25]. A decreased Efficiency of Autologous Egg Cryopreservation: Eight Years' Experiences and Clinical Outcomes DOI: http://dx.doi.org/10.5772/intechopen.98675 tendency in live birth rate was observed in women >37 years as compared with women ≤37 years old.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In the present study, when we analyzed the efficiency of oocyte cryopreservation in women at different age groups, we found that live birth rates can reach to 51.1, 46.7 and 28.6% in women <35, 35-37, and > 37 years old, respectively, with their first embryo transfer (fresh), which is comparable to live birth rates with embryo transfer from fresh oocytes in our clinic or other published data [2,3,9,23,25]. A decreased Efficiency of Autologous Egg Cryopreservation: Eight Years' Experiences and Clinical Outcomes DOI: http://dx.doi.org/10.5772/intechopen.98675 tendency in live birth rate was observed in women >37 years as compared with women ≤37 years old.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, women's age at the time of oocyte cryopreservation is the most important factor affecting live birth rates. Present and previous data [3,9,[16][17][18] suggest that women should preserve their oocytes before 37 years old if they plan to rely on oocyte cryopreservation to have a live birth. However, for the women who are more than 37 years old, it is still possible to have their oocytes to be cryopreserved for future use, but success mainly relies on oocyte quality and number [3,9,13].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations